L'emergenza Covid-19 tra comunicazione e formazione - Cosimo Di Bari (Firenze University Press, 2020)
The global spread of the Covid-19 Virus has generated a cultural earthquake, that has healty, economical, professional, social consequences. The article, starting from a pedagogical perspective, reflects on some of the profound changes which have occurred in the last few months, immersing humanity in a situation more and more similar to the "postmodern condition". The text inquires particularly into the authority and reliability of the medias; the changes of identity between local and global and the relationship between school (even from nursery) and technology.